Farmers' identity, property rights cognition and perception of rural residential land distributive justice in China: Findings from Nanjing, Jiangsu Province. (September 2018) - Wang, Yurong; Chen, Ligen; Long, Kaisheng
Abstract: Justice in rural residential land distribution is vital to both farmers' living security and social stability in China. Based on the Self-interest Theory and endowment effect, this article discusses the impact of farmers' identity and property rights cognition on their perceptions of rural residential land distributive justice using the survey data of 565 rural households in Nanjing, Jiangsu province, China by principal component analysis and binary logistic regression. The results indicate that (1) farmers' identity would impact their perceptions of rural residential land distributive justice, among different farmers, perceptions of rural residential land distributive justice differed greatly; (2) there is a negative relationship between farmers' perceptions of rural residential land distributive justice and their private property rights cognition; (3) farmers' private property rights cognition would be an amplifier to the impact of their identity on rural residential land distributive justice perceptions. We finally argue that rural residential land policy judgment about injustice should focus on farmers' identity, and the government should protect legitimate rights and interests of farmers in the process of rural residential land distribution. Highlights: A framework of rural residential land distributive justice is established. An empirical research is conducted using data from Nanjing, Jiangsu Province, China. Farmers' identity and property rights cognition are influencing factors in this study. Farmers' rights and interests in rural land distribution should be protected.